Differential expression of the ICF (immunodeficiency, centromeric heterochromatin, facial anomalies) mutation in lymphocytes and fibroblasts. Issue 7 (July 1989) - Maraschio, P; Tupler, R; Dainotti, E; Piantanida, M; Cazzola, G; Tiepolo, L
Abstract : Fibroblasts from a patient with ICF syndrome were grown in the presence of excess of nucleotides, in media with different amounts of folic acid, and with caffeine in an attempt to induce the chromosomal anomalies observed in lymphocytes. We induced despiralisation and breakages in the centromeric heterochromatin of chromosomes 1 and 16 but not associations and multibranching. We suggest that the absence of the major chromosomal anomalies in fibroblasts from patients with ICF might be the result of both a longer G2 in these cells and differential patterns of interphase heterochromatin associations in the two tissues.